2015
DOI: 10.1038/bjc.2015.340
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic potential of serum miR-7, miR-16, miR-25, miR-93, miR-182, miR-376a and miR-429 in ovarian cancer patients

Abstract: Background:Owing to late diagnosis in advanced disease stages, prognosis of patients with epithelial ovarian cancer (EOC) is poor. The quantification of deregulated levels of microRNAs could facilitate earlier diagnosis and improve prognosis of EOC.Methods:Seven microRNAs (miR-7, miR-16, miR-25, miR-93, miR-182, miR-376a and miR-429) were quantified in the serum of 180 EOC patients and 66 healthy women by TaqMan PCR microRNA assays. Median follow-up time was 21 months. The effects of miR-7 and miR-429 on apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 42 publications
8
86
0
Order By: Relevance
“…The normalized data were statistically evaluated and compared with the clinical parameters of EOC patients. In addition, we selected miR‐200b and miR‐320 for further in vitro and functional analyses because they were significantly deregulated in exosomes from plasma of EOC patients, and their dual character as tumor suppressor genes and oncomiRs with multiple cancer‐specific functions have been described in diverse studies (Li et al ., ; Meng et al ., ; Muralidhar and Barbolina, ; Wang et al ., ). We quantified the levels of these two miRNAs in two cell lines (OVCAR3 and SKOV3) and in exosomes released from these cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The normalized data were statistically evaluated and compared with the clinical parameters of EOC patients. In addition, we selected miR‐200b and miR‐320 for further in vitro and functional analyses because they were significantly deregulated in exosomes from plasma of EOC patients, and their dual character as tumor suppressor genes and oncomiRs with multiple cancer‐specific functions have been described in diverse studies (Li et al ., ; Meng et al ., ; Muralidhar and Barbolina, ; Wang et al ., ). We quantified the levels of these two miRNAs in two cell lines (OVCAR3 and SKOV3) and in exosomes released from these cells.…”
Section: Resultsmentioning
confidence: 99%
“…MiR‐16 may also be a potential therapeutic target and clinical biomarker of bone metastasis, because it is elevated in osteoclast differentiation and bone metastasis (Ell et al ., ). In our present study, we found that lower amounts of miR‐16 were packaged in exosomes from EOC patients, while in our previous study, we detected that the serum levels of circulating miR‐16 were neither up‐ nor downregulated in EOC patients compared with healthy women (Meng et al ., ). Moreover, we observed that the decreased levels of miR‐16 in exosomes from EOC patients further decreased in recurrent patients, suggesting that decrease in levels of exosomal miRNAs is particularly associated with recurrence.…”
Section: Discussionmentioning
confidence: 97%
“…Although the qPCR validation test on miR-93 expression level has been conducted in the previous studies, 57,58,61,62 to our best knowledge, our study is still the first to research miR-93 expression in pan-cancer. In the validation test, the serum miR-93 expression level was detected in 14 cancers and six benign lesion types.…”
Section: Discussionmentioning
confidence: 98%
“…Separately, 11 studies from eight articles 15,[56][57][58][59][60][61][62] were included in the diagnostic meta-analysis and 14 studies from 13 articles 15,24,29,41,47,51,[63][64][65][66][67][68][69] were included in the prognostic meta-analysis. After screening the titles and abstracts, 476 articles were excluded because they were reviews (n = 18), meta-analyses (n = 5), nonhuman studies (n = 14), or studies irrelevant to our topic (n = 439).…”
Section: The Basic Characteristic Of Meta-analysismentioning
confidence: 99%
“…Recently, several studies have reported that some microRNAs were elevated or decreased in the serum of GC patients compared to healthy controls [7,8]. These different expressed microRNAs may be potential biomarkers for GS diagnosis [7,9,10].…”
Section: Introductionmentioning
confidence: 97%